DETERMINANTS OF NON-PERFORMING FINANCING CASE STUDY : 10 SHARIA BANKS IN INDONESIA PERIODS OF 2011:1 – 2015:1 - Felisma Choirunnisa (EKPI 15 UMY 227, 2015)
*227 This study examines the determinants of the non-performing financing (NPF) ratio and analyzes which indicators are the most influential on NPF ratio of Indonesia sharia bank. This paper finds that the level of NPF ratio can be attributed to both macroeconomic conditions and banks’specific factors in 10 Indonesia sharia banks during the first quarter of 2011 to the first quarter of 2015. The independent variables used in this study are Return on Equity (ROE) and Capital Adequacy Ratio (CAR) as the bank-specific indicators and inflation rate as the macroeconomic indicator. This paper uses two methods of panel data regression which are the Fully Modified Least Squares (FMOLS) where the coefficient describes a long-term relationship and the Ordinary Least Squares (OLS). Both method results show that there is a negative and significant relationship between ROE and CAR, while the panel FMOLS method shows that the inflation rate has no significant effect on the NPF ratio.The results also indicate that based on those two methods, bank-specific factors such as ROE and CAR has stronger effect on the NPF ratio than the macroeconomic indicator which is inflation rate.